2017
DOI: 10.1016/j.bbrc.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase inhibitor sivelestat ameliorates gefitinib-naphthalene-induced acute pneumonitis in mice

Abstract: Gefitinib, an epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI), is an effective therapeutic agent for non-small cell lung cancer with EGFR mutations. It can cause severe acute pneumonitis in some patients. We previously demonstrated that mice with naphthalene-induced airway epithelial injury developed severe gefitinib-induced pneumonitis and that neutrophils played important roles in the development of the disease. This study aimed to investigate the effects of the neutrophil elastase inhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the present study, 40 mg/kg sivelestat were intraperitoneally administered to mice every 6 h, resulting in significantly decreased NE activity in BALF and markedly reduced mortality of mice inoculated with S. pneumoniae compared with untreated control mice. Yanagihara et al demonstrated that administration of sivelestat (30 mg/mL per 12 h) resulted in moderately delayed mortality in pneumococcal pneumonia mouse model ( 14 ), whereas Mikumo et al reported that administration of 150 mg/kg/day of sivelestat ameliorates pneumonitis and that there is significant improvement in the survival of mice administered naphthalene and gefinitib ( 46 ). Higher dose or increased frequency of administration could have effectively blocked NE activity in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 40 mg/kg sivelestat were intraperitoneally administered to mice every 6 h, resulting in significantly decreased NE activity in BALF and markedly reduced mortality of mice inoculated with S. pneumoniae compared with untreated control mice. Yanagihara et al demonstrated that administration of sivelestat (30 mg/mL per 12 h) resulted in moderately delayed mortality in pneumococcal pneumonia mouse model ( 14 ), whereas Mikumo et al reported that administration of 150 mg/kg/day of sivelestat ameliorates pneumonitis and that there is significant improvement in the survival of mice administered naphthalene and gefinitib ( 46 ). Higher dose or increased frequency of administration could have effectively blocked NE activity in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the alveolar epithelium is able to contribute to the immune landscape of the lung by generating pro-inflammatory cytokines like CXCL10 and CCL2 when stimulated with IFNλ [46] . Studies to investigate the effects of gefitinib on airway repair after injury demonstrated that mice treated with gefitinib after naphthalene induced airway injury developed severe pneumonitis driven primarily by infiltrating neutrophils [47,48] . Bronchial epithelial cells harvested from these mice demonstrated an increase in proinflammatory genes.…”
Section: Role Of the Tumor Immune Microenvironment In Dictating Immunmentioning
confidence: 99%
“…Pharmacologic inhibition of NE has been shown to successfully reduce the inflammatory response and disease severity in different pathologies mediated by acute inflammation . As we and others demonstrated a pronounced acute inflammatory response in AILI, and given the increased production of NE, we hypothesized that NE inhibition may be protective against AILI.…”
Section: Resultsmentioning
confidence: 88%
“…injected with PBS or 300 mg/kg of APAP (Sigma, Diegem, Belgium) dissolved in warmed PBS, after overnight fasting. Two hours after APAP injection, mice received either PBS vehicle, sivelestat (150 mg/kg i.p., dissolved in PBS, Tocris, Abingdon, United Kingdom), NAC (200 mg/kg i.p., dissolved in PBS, Sigma), or the combination of sivelestat and NAC (separate injections), creating five study groups ( n = 8 in each group). Dose regimens were based on published protocols.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation